Which urban agriculture conditions enable or constrain sustainable food production? - Lee, S.; Shin, S.; Lee, H.; Park, M.S. (Informa UK Limited, 2023)
Urban agriculture (UA) has been adopted as a strategy for food security in urban areas. This study identified the conditions for development of UA through a systematic review of UA case studies. It classified the enabling and constraining conditions within the three compositional elements of UA – necessity, ability, and opportunity – and determined the primary and secondary conditions for UA design by the country income group. The following conditions are required for both high-income and low/ middle-income countries: Motivation/public awareness; labour/human resources; policy and institutional infrastructure; social capital; and arable land and resources for farming. Agricultural education/training and research and technical development are needed for low and middle-income countries as the key secondary conditions. In high-income countries, a lack of farmers’ knowledge and urban development are the main challenges to UA implementation. Therefore, the research findings could be meaningful evidence for making decisions and designing UA policies for sustainable food production.